2001
DOI: 10.1063/1.1399024
|View full text |Cite
|
Sign up to set email alerts
|

Physical and electrical properties of Ge-implanted SiO2 films

Abstract: Metal–oxide–semiconductor structures with a Ge nanocrystal embedded in SiO2 films were fabricated by Ge+ ion implantation and subsequent high-temperature annealing. The Raman spectra indicate the evidence of self-assembled Ge nanocrystals in the SiO2 films. The Ge size and its density were estimated to 3–5 nm and 1×1012/cm2, respectively. Photoluminescence spectra showed a strong blue–violet band around 400 nm and a weak near-infrared band around 750 nm, respectively. The several implantation-induced deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…where D is the intensity prefactor, jC(O,q)j 2 is the Fourier coefficient of the phonon confinement function, x(q) is the phonon dispersion, and C 0 is the inverse lifetime of the phonon in bulk carbon [5]. We focus on the G-band position, which is related to the fraction of sp 2 -bonded atomic sites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where D is the intensity prefactor, jC(O,q)j 2 is the Fourier coefficient of the phonon confinement function, x(q) is the phonon dispersion, and C 0 is the inverse lifetime of the phonon in bulk carbon [5]. We focus on the G-band position, which is related to the fraction of sp 2 -bonded atomic sites.…”
Section: Resultsmentioning
confidence: 99%
“…Nanocrystal (nc) in the MIS structure have memory characteristics in which charge storage is strongly influenced by several mechanism including quantum confinement effects, Coulomb charge effects, traps at interface and defect states [3][4][5][6]8,9]. It has been reported that electrons injected into nc might fall into a shallow traps near the conduction band edge [3,8].…”
Section: Introductionmentioning
confidence: 99%
“…Also, a new luminescence band at about 850 nm appears at 900°C. This infrared band has been ascribed to the formation of Ge nanocrystals which give light emission owing to the quantum confinement effect [5]. Therefore, the 900°C luminescence data might indicate that coalescence of Ge atoms/ clusters near melting state not only generates Ge nanocrystals, but also enhances formation of Ge-related luminescent centers, which might locate at nanocrystal surfaces since surface-to-volume ratio at nanometer scale for precipitates is greatly enlarged.…”
Section: Discussionmentioning
confidence: 98%
“…Recently there is also an increasing interest in the electronic properties and performance characteristics of memory devices containing germanium (Ge) nanocrystals which were synthesized using various methods [7][8][9][10][11][12][13]. The device performance and reliability will depend on many factors, such as the ability to control nanocrystal size, size distribution, crystallinity, areal density, oxide-passivation quality, and the crystal-to-crystal insulation that prevents lateral charge conduction in the nanocrystal layer [5].…”
Section: Introductionmentioning
confidence: 99%